2020
DOI: 10.1002/er.5781
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous production of hydrogen and carbon nanotubes from cracking of a waste cooking oil model compound over Ni‐Co / SBA ‐15 catalysts

Abstract: Hydrogen is considered an ideal energy carrier. However, the use of fossil fuels to produce hydrogen depletes natural resources and causes environmental problems. Therefore, there is an urgent need to find alternative raw materials and technologies for the production of hydrogen. Waste cooking oil (WCO) is a renewable energy source that has emerged as a potential raw material for hydrogen production. This study describes the production of hydrogen and carbon nanotubes (CNTs) by catalytic cracking of a WCO mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Williams, for instance, reviews the formation of hydrogen and carbon nanotubes from plastic waste, [219] and Liu and Yuan describe the same products from cracking model compounds representing waste cooking oil. [220] The carburisation of biomass and plastics, but also of hydrocarbons, such as methane, may be an interesting option to prepare so-called "turquoise" hydrogen without producing CO 2 . Ma et al describe the structural effects of regeneration of coked catalysts used for lignin pyrolysis using NMR and electron microscopy, [221] but do not analyse the coke species themselves.…”
Section: Catalytic Conversion Of Municipal and Agricultural Wastementioning
confidence: 99%
See 1 more Smart Citation
“…Williams, for instance, reviews the formation of hydrogen and carbon nanotubes from plastic waste, [219] and Liu and Yuan describe the same products from cracking model compounds representing waste cooking oil. [220] The carburisation of biomass and plastics, but also of hydrocarbons, such as methane, may be an interesting option to prepare so-called "turquoise" hydrogen without producing CO 2 . Ma et al describe the structural effects of regeneration of coked catalysts used for lignin pyrolysis using NMR and electron microscopy, [221] but do not analyse the coke species themselves.…”
Section: Catalytic Conversion Of Municipal and Agricultural Wastementioning
confidence: 99%
“…The analysis of carbon species during the conversion of biomass and plastics, illustrated in Figure 16, seems to focus more on the products formed than on catalyst deactivation. Williams, for instance, reviews the formation of hydrogen and carbon nanotubes from plastic waste, [219] and Liu and Yuan describe the same products from cracking model compounds representing waste cooking oil [220] . The carburisation of biomass and plastics, but also of hydrocarbons, such as methane, may be an interesting option to prepare so‐called “turquoise” hydrogen without producing CO 2 .…”
Section: Analysis Of Carbon Depositsmentioning
confidence: 99%
“…The content of hydrogen and carbon monoxide increased with shorter residence times, while the content of methane and ethane in the gas phase decreased [67]. Liu and Yuan [101] studied the catalytic pyrolysis of waste cooking oil. They found that the yield of hydrogen decreased from 42 to 31 vol% when residence time was 4 h, which indicated a decrease in catalyst activity over time.…”
Section: Influence Of External Conditions On the Characteristics Of T...mentioning
confidence: 99%
“…Catalytic pyrolysis of waste cooking oil was investigated by Liu et al [101]. The effect of nickel-cobalt catalyst and reaction temperature on hydrogen production was studied.…”
Section: Specialized Additives and Catalysts To Increase The Efficien...mentioning
confidence: 99%
“…Fe, Co, and Ni are commonly selected as catalysts to enhance the different carbon sources for the formation of carbon nanomaterials [ 8 , 31 , 32 ]. In addition, nickel- and cobalt oxides-impregnated SBA-15 materials presented resistance to coke formation, with high activity and selectivity, and were applied to organic solvents (cyclohexane, n-hexane, propane, and CO) [ 33 ] and biomass-derived fuels (such as liquid hydrocarbons and diesel-range hydrocarbons) [ 34 , 35 ], the growth of carbon nanofibers [ 36 ], bio-oil to produce hydrogen and carbon nanotubes [ 37 ], and n-hexane, propane and CO oxidation [ 38 ]. Some literature indicated higher performance in converting methyl esters to produce green diesel (C11-C20 hydrocarbons) [ 39 ].…”
Section: Introductionmentioning
confidence: 99%